Effect of Argon-Oxygen Mixing Gas during Magnetron Sputtering on TiO2 Coatings - N. Madaoui; L. Bait; K. Kheyar; N. Saoula (Advances in Materials Science and Engineering)
A reactive r.f magnetron sputtering method was used to deposit titanium dioxide coating on stainless steel substrates without intentional heating or biasing. The purpose of this work is given to study the argon-oxygen mixing gas on the corrosion behavior of TiO2 coatings. The morphology and structure of the coatings were studied by X-ray diffraction (XRD). Potentiodynamic polarization was used to study the corrosion behavior of the coatings. The results obtained from potentiodynamic polarization curves showed that TiO2 coatings possessed higher corrosion resistance than uncoated substrate.